Probing T Cell 3D Mechanosensing With Magnetically-Actuated Structures - Sachar, Chirag; Kam, Lance C. (Frontiers in Immunology, 2021)
The ability of cells to recognize and respond to the mechanical properties of their environment is of increasing importance in T cell physiology. However, initial studies in this direction focused on planar hydrogel and elastomer surfaces, presenting several challenges in interpretation including difficulties in separating mechanical stiffness from changes in chemistry needed to modulate this property. We introduce here the use of magnetic fields to change the structural rigidity of microscale elastomer pillars loaded with superparamagnetic nanoparticles, independent of substrate chemistry. This magnetic modulation of rigidity, embodied as the pillar spring constant, changed the interaction of mouse naïve CD4+ T cells from a contractile morphology to one involving deep embedding of cells into the array. Furthermore, increasing spring constant was associated with higher IL-2 secretion, showing a functional impact of this mechano sensing. The system introduced here thus separates local substrate stiffness and long-range structural rigidity, revealing new facets of T cell interaction with their environment.